HUBUNGAN MOTIVASI KERJA DAN SUPERVISI KEPALA SEKOLAH DENGAN KINERJA GURU SMP NEGERI DI KECAMATAN BABAHROT ACEH BARAT DAYA - Afdhal Jihad; Murniati AR; Yusrizal . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
Human resources become the main key in realizing quality education. This study aims to (1) Know the Work Motivation relationship with Teacher Performance SMP Negeri Babahrot Aceh Barat Daya; (2) Determine the relationship Supervising Principal Teacher Performance SMP Negeri Babahrot Aceh Barat Daya; (3) Knowing relationship Work Motivation and Supervision Principal with teacher performance SMP Negeri Babahrot Aceh Barat Daya. This research uses quantitative approach. Which became a population of 891 students and 85 teachers, the samples were 208 students and 65 teachers at SMP Negeri Babahrot Aceh Barat Daya. In changing the data used Method of Successive Interval  and analyze data used SPSS application. Results of the study are (1) There is a correlation between motivation and performance of SMP Negeri Babahrot Aceh Barat Daya value test results for 0,579 on the S ig (2-tailed) = 0,000; (2) There is a strong correlation between principal supervision and performance SMP Negeri Babahrot Aceh Barat Daya with test result value of 0.722 on sig (2-tailed) = 0,000; (3) The correlation coefficient test (R) shows the value of 0.753 which means work motivation and supervision gives 75.3% influence on teacher performance improvement. While the rest of 24.7% influenced by other things. So the performance of teachers is strongly influenced by Work Motivation and Headmaster Supervision. Keywords: work motivation, principal’s supervisory, and teachers’ job performances